PROGRAM PENDAMPINGAN "PERENCANAAN KEUANGAN KELUARGA: MEWUJUDKAN KEUANGAN SEHAT" BAGI KARYAWAN PT SEKAWAN ADHYA CORPORINDO SEBAGAI BENTUK CORPORATE SOCIAL RESPONSIBILITY - Shinta Maharani Trivena; Tsabita Karima (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program by Tim Jasasekawan aimed to improve financial literacy and well-being of 15 cleaning service employees at PT Sekawan Adhya Corporindo through interactive training and practical mentoring as part of the company's Corporate Social Responsibility initiative. The program addressed employees' needs for better financial management skills, including budgeting, saving strategies, debt management, and emergency fund planning. The implementation method included three main training sessions on October 10, 2025, at UB Guest House Malang, covering basic financial planning, debt management and emergency funds, and insurance basics, followed by a flexible coordinated savings system. Pre-test results showed opportunities for improvement in financial literacy, particularly in understanding interest rates and debt management. Post-test results demonstrated significant improvement (from 49.33% to 82%) in financial knowledge and awareness. The program successfully equipped employees with practical knowledge for better family financial management and strengthened the company's commitment to employee welfare.